ANALISA KOEFISIEN ABSORPSI BUNYI MATERIAL SERAT BATANG KELAPA SAWIT DENGAN GYPSUM MENGGUNAKAN SONIC WAVE ANALYZER - Qory Gunanda; Riad Syech; Muhammad Edisar (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has  been done  in  analyzing  a coefficient absorption of composite material of oil palm trunk fiber and gypsum using a sonic wave analyzer (SOWAN) and carried out using sound  wave of 150 Hz frequency.  Sample  was formed  as  a  cylinder made from gypsum  with  3:5  ratio  of water and gypsum,  formed  a  pipe with  7,5 cm  outer  diameter and heights  of 2 cm, 3 cm, 4 cm, 5 cm, and 6 cm (sample    thickness). The  pipe with the outer  diameter  of  6 cm  was used  for  making  a  cavity  in  the  samples  and  then the composed of oil palm trunk fiber of ± 1 cm length with the variation percentage of fiber of 12,24%, 24,48%, 36,73%, and 48,97% filled in to each sample. Ao (initial amplitude) and A (final  amplitude)  then  were  measured by  Sonic Wave  Analyzer (SOWAN) with the intensity  of  65 dB, 70 dB, 75 dB, dan 80 dB.  Results  of the measurements  showed that the bigger  percentation  of fiber,  the higher  coefficient of sound  absorption andthicker sample  produced  bigger the coefficient of sound absorption.  The biggest absorption  coefficient  was  0,4957,  due to the  sample with 6  cm thickness when the intensity  was  80 dB and the smallest  absorption  coefficient was  0,3088,  of the  sample with 2 cm thickness  when the intensity  was  65 dB. The maximum  absorptioncoefficients of the sample thickness of 2 cm, 3 cm, 4 cm, and 5 cm were 0,3557, 0,3779,0,4155,  and  0,4863,  respectively.  This  showed that  preparing the sample by method  ofarranging the oil palm stem's fiber inside the sample  was  more effective to  absorb  the sound for low frequencies (150Hz) if viewed from the standard of absorption coefficientof  gypsum  was  0.29  for  frequency  of  150  Hz.  Based on  the  results of  this study  the absorption  coefficients  exceed  the  minimum  limit  0.15  as suggested  ISO 11654 as a silencer.